2004
DOI: 10.1097/00000542-200404000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Bicoherence Is Sensitive to Noxious Stimuli during Isoflurane or Sevoflurane Anesthesia

Abstract: Noxious stimuli decreased the peak heights of electroencephalographic bicoherence, an effect that was counteracted by fentanyl analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 14 publications
3
61
2
1
Order By: Relevance
“…pentazocine, given as a 0.3 mg/kg bolus before surgery under nitrous oxide-sevoflurane anesthesia, provoked a statistically significant increase in BIS values, in contrast previous reports on the effects of other opioids [1,2]. In a preliminary study involving eight patients in which 1% sevoflurane alone was inhaled, we also observed a significant increase (from 49.3 ± 5.8 at baseline to 64.9 ± 2.8 at 15 min from baseline) in the BIS values following i.v.…”
contrasting
confidence: 85%
See 3 more Smart Citations
“…pentazocine, given as a 0.3 mg/kg bolus before surgery under nitrous oxide-sevoflurane anesthesia, provoked a statistically significant increase in BIS values, in contrast previous reports on the effects of other opioids [1,2]. In a preliminary study involving eight patients in which 1% sevoflurane alone was inhaled, we also observed a significant increase (from 49.3 ± 5.8 at baseline to 64.9 ± 2.8 at 15 min from baseline) in the BIS values following i.v.…”
contrasting
confidence: 85%
“…Many investigators have reported that opioids produce minimal changes in bispectral index (BIS) values in the absence of painful stimulation [1,2] but that the addition of opioids to anesthetics does affect BIS values when a painful stimulus is applied. However, despite the large number of published reports on the effects of mu opioids, such as fentanyl and remifentanil, on the BIS during general anesthesia [1,2], no comparative studies on pentazocine, a kappa agonist, versus fentanyl, a mu agonist, on the BIS values have been reported.…”
Section: Abstract Pentazocine á Fentanyl á Bispectral Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also shown that we can obtain other facts from phase information. 4 Bispectral analysis would have given more information than power spectral-based analysis, if the authors had used the EEG recorded from unilateral leads.…”
mentioning
confidence: 99%